Portuguese born globals: an exploratory study - Simões, Vítor Corado (2001)
In the so-called Uppsala model internationalisation is envisaged as an incremental process where the acquisition of experimental knowledge acts as a catalyst for decisions of further resources commitment in international markets. In the last decade, however, a new host of firms emerged, significantly challenging established theoretical approaches. These firms, often labelled born globals, take a worldwide business approach since inception, and swiftly get a global reach, relying on a mix of different cooperative arrangements and modes of operation. Their organisational structures are usually less hierarchical than those prevailing in established multinational enterprises. The present paper provides a conceptual framework to understand this phenomenon. It emerged in a business environment characterised by globalisation, liberalisation and technical change. Entrepreneurial capabilities, together with the management of knowledge intensive resources and relational capital, enable the design of a unique, distinctive concept which may be exploited through focussing in a global niche. The framework was applied to analyse the development of three Portuguese firms, two from the software and one from the footwear industry. It was found that born globals are not specific to technology-intensive sectors and that the framework is a good tool for better understanding born globals emergence and growth.